Evaluation drag coefficients for circular patch vegetation with different riverbed roughness. Issue 1 (31st December 2022) - Gubashi, Karim R.; Mulahasan, Saad; Jameel, Mohammed Abid; Al-Madhhachi, Abdul-Sahib T.
Abstract: The drag coefficient of a one-line circular patch of emergent sparse vegetation in an open-channel flow or riverbeds with varying bed roughness sizes was experimentally investigated. The total roughness of the channel was accounted for using the rate of energy dissipation that incorporated resistance by bed particles and cylinder obstacles. A total of 48 flume experiments were conducted by varying the flow rate, bed roughness, and water depth. The analysis of flow resistance due to the one-line patch of sparse vegetation and the variation in bed roughness was achieved through dimensional analysis. The results show that the drag coefficient Cd is a function of stem Reynolds number, Rd, Froude number, Fr, and the ratio between stem diameter and flow depth (d/H). Experiments showed that the drag coefficient varied with the stem Reynolds number, Froude number, and bed roughness. The Cd generally increased with decreasing stem Reynolds number and Froude number, and this increase in drag coefficient appeared significant for a rough bed of large particles. Results showed that Reynold numbers for different bed roughness had a minimal influence on the drag coefficients. The Fr increases as bed materials are smoother. Statistical regression analysis was achieved to drive the relationship between drag coefficient versus Rd, Fr, and d/H with a coefficient of determination of more than 0.97.